1997
DOI: 10.1037/1076-8971.3.4.589
|View full text |Cite
|
Sign up to set email alerts
|

What social science teaches us about the jury instruction process.

Abstract: This article critically examines the social science research relevant to evaluating the effectiveness of judicial instructions. For several decades it has been shown repeatedly that jurors' comprehension of instructions is poor. Consequently, factors that contribute to instruction ineffectiveness are examined. In addition to focusing on the general problem of instruction comprehension, this article reviews limitations associated with a variety of specific types of instructions. Fortunately, several solutions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 86 publications
1
83
0
Order By: Relevance
“…One major source of information is the instructions given by the judge, which provide jurors with a legal context to guide their decision making (Liberman & Sales, 1997). However, any effect of jury instructions depends upon the judge heror himself not hosting corresponding biases and stereotypes or, if so, that the judge's instructions are not accompanied by nonverbal behavior that conveys the stereotype (Halverson et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…One major source of information is the instructions given by the judge, which provide jurors with a legal context to guide their decision making (Liberman & Sales, 1997). However, any effect of jury instructions depends upon the judge heror himself not hosting corresponding biases and stereotypes or, if so, that the judge's instructions are not accompanied by nonverbal behavior that conveys the stereotype (Halverson et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, for a decision to be classified as nullification, it should be shown that the jurors comprehended the jury instructions and, nevertheless, decided to disregard them. Many studies have shown that jurors often do not understand the instructions given to them by the judge (e.g., see Lieberman & Sales, 1997Shaffer & Wheatman, 2000). If a verdict results from the jurors' misunderstanding of the judge's instructions, then this cannot be classed as willful defiance of those instructions.…”
mentioning
confidence: 96%
“…72 In the present study, using a revised version of the same basic trial, the opposite occurred-recipients of nullification instructions were more likely to convict when the victim was relatively unsympathetic. While there were many differences in the trial content and mode of presentation between the two studies, 73 it is still noteworthy that the bad character of the victim served 68 See Lieberman & Sales (1997) for a review. 69 E.g., Barrett et al (2001); Schwarz & Clore (1996) 70 E.g.…”
Section: Discussionmentioning
confidence: 97%